2020
DOI: 10.1038/s41598-020-69422-z
|View full text |Cite
|
Sign up to set email alerts
|

Significant correlation between plasma proteome profile and pain intensity, sensitivity, and psychological distress in women with fibromyalgia

Abstract: Fibromyalgia (FM) is a complex pain condition where the pathophysiological and molecular mechanisms are not fully elucidated. The primary aim of this study was to investigate the plasma proteome profile in women with FM compared to controls. The secondary aim was to investigate if plasma protein patterns correlate with the clinical variables pain intensity, sensitivity, and psychological distress. Clinical variables/background data were retrieved through questionnaires. Pressure pain thresholds (PPT) were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 69 publications
9
48
0
Order By: Relevance
“…We and others have reported marked significant differences both in blood and in muscle proteomes between CWP/FM and healthy controls [10,[23][24][25][26]. Moreover, both muscle and plasma protein patterns show strong significant correlations with pain intensity [25,27,28].…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…We and others have reported marked significant differences both in blood and in muscle proteomes between CWP/FM and healthy controls [10,[23][24][25][26]. Moreover, both muscle and plasma protein patterns show strong significant correlations with pain intensity [25,27,28].…”
Section: Introductionmentioning
confidence: 67%
“…The strongest regression was obtained using proteomics. Recently, we reported that plasma proteins correlated with PPT in an FM cohort [25].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations